Physicochemical and Electronic Properties of Cationic [6]Helicenes: from Chemical and Electrochemical Stabilities to Far‐Red (Polarized) Luminescence. Issue 51 (25th November 2016) - Bosson, Johann; Labrador, Geraldine M.; Pascal, Simon; Miannay, François‐Alexandre; Yushchenko, Oleksandr; Li, Haidong; Bouffier, Laurent; Sojic, Neso; Tovar, Roberto C.; Muller, Gilles; Jacquemin, Denis; Laurent, Adèle D.; et al.
Abstract: Invited for the cover of this issue is the group of Eric Vauthey and Jérôme Lacour. The image depicts a chiral cationic [6]helicene, which is a powerful dye and fluorophore emitting circularly polarized light in the red to far red region. Read the full text of the article at 10.1002/chem.201603591 . Abstract : " Every time a new color appears on the walls of a chromatography column, collaborators talk to each other ." Read more about the story behind the cover in the Cover Profile and about the research itself on page 18394 ff. (DOI:10.1002/chem.201603591 ).